AB1017 WHAT IS THE CURRENT SITUATION OF THE PAEDIATRIC RHEUMATOLOGY TRANSITION CARE UNITS?. (June 2019) - Martín-Varillas, José Luis; Clemente, Daniel; López Robledillo, J.C.; Benavente, Belén Serrano; Monteagudo, Indalecio; Nieto, Juan Carlos
Abstract : Background: Switching from paediatric rheumatology to the adult rheumatology care units has a negative impact on disease control and adherence in young patients with juvenile idiopathic arthritis (JIA) but also in other chronic diseases. Transitional care services provide the opportunity of being followed-up by an adult rheumatology specialized in juvenile rheumatic diseases. Objectives: In our study we report the current situation of a rheumatology transition care unit (RTCU). Methods: We set up an observational and retrospective study of patients followed in our unit between September 2015 and December 2018. We included those patients with a disease beginning at 16 years or younger and those patients who were attended on RTCU for the first time before age 25. Clinical and demographic data and all treatments received by the patients before and after de first visit in the transition care unit were also collected. Results: 119 patients were attended in our RTCU. After applying the exclusion criteria, 110 patients remained: 78 female/32 male (70.9/29.1%) with a median age of 18.5 [17.9-19.8] years at the first visit. No significant differences in age at the first visit were found between the first (September-2015 to September-2017) and the second stage (October-2017 to December-2018), 18.7 (17.8-20.2) vs. 18.2 (17.9-18.6) years respectively. The most frequent diagnoses are included in the table 1 . Of the 75 patients with JIA, 54 were women (72%) with a median age at the disease onset of 6.88 [2.3-12.7] and 21.3% of patients had chronic anterior uveitis. 22 patients (29.3%) presented joint or ocular inflammatory activity or flare at the time of transition first visit but only 1 patient maintained inflammatory activity during the 3 years of follow-up. A total of 64 patients (85.3%) with JIA diagnosis were under treatment with synthetic DMARD, mostly methotrexate (61) or leflunomide (7). In addition, 43 patients (57.3%) required biological DMARD in the past, and 8 of them (10.7%) required more than one. The most frequently used drugs were: etanercept (ETN) (29 patients) and adalimumab (ADA) (19 patients). Tocilizumab (TCZ) (4), abatacept (1) and infliximab (1) were also used. Of these patients, at the time of the first visit on RTCU, 24 (32%) had no treatment, 42 patients (56%) had synthetic DMARD and 34 patients (45.3%) had biologic therapy in monotherapy or combined with DMARDs (19 ETN, 12 ADA, and 3 TCZ). Conclusion: RTCU assessed mainly patients with JIA and connective tissue diseases. Most patients were inactive during the transfer to the adult unit, but the existence of patients that were still active and/or needed treatment with synthetic and/or biological DMARD reaffirms the need for close control in this period. Disclosure of Interests: None declared